37.4k views
4 votes
(Quadratic) What is the answer to this quadratic

(Quadratic) What is the answer to this quadratic-example-1

2 Answers

1 vote

Answer:


x_(1) = (2+√(192))/(-4); x_(2) = (2-√(192))/(-4)

Explanation:


-2a^(2)-2b-12=0\\

Take the coefficients and substitute for a, b and c


a = -2; b = -2; c = -12


x_(1,2) = (-b +- √(b^2 - 4ac) )/(2a)


x_(1,2) = (2+-√(2^2-4*-2*-12))/(2*-2)


x_(1) = (2+√(192))/(-4)


x_(2) = (2-√(192))/(-4)

Please tell me if my solutions are incorrect so I can fix them.

User Huma Ali
by
4.9k points
2 votes
2a^2+2b-12=0 is not a solvable quadratic. I will assume you meant 2x^2+2x-12
The quadratic formula is (-b+-sqrt(b^2-(4ac))/2a

(-2+-sqrt(2^2-(4*2*-12))/2*2
(-2+-sqrt(4-(-96))/4
(-2+-sqrt(100))/4
(-2+-10)/4
12/4 or 8/4
3 or 2
The answer is x=3 or x=2
User Joanny
by
5.7k points